ACUPUNCTURE AND SELF ACUPRESSURE TREATMENT OF HEMIFACIAL SPASM: A CASE REPORT - Septriana, Maya; Perdana, Yudi (Journal of Vocational Health Studies, 2020)
Background: Hemifacial spasm (HFS) is a condition of unilateral, involuntary, irregular, spasmodic movements of the face. The condition is most commonly a result of vascular loop compression at the root entry zone of the facial nerve. Patient whose hemifacial spasm with  left-sided facial complaints often twitching since 6 months ago. This   69-year-old  man with hyperlipidemia and hypertension had diagnosed with hemifacial spasm by neurologist. Purpose: To prove the effect of acupuncture on Fengchi (GB 20), Neiguan (PC 6) and Taichong (LR 3) accompanied with acupressure on Taichong (LR 3)  and auricular acupressure on the Ear Shenmen point in patient with hemifacial spasm. Method: Handling Hemifacial spasm with acupuncture on Fengchi (GB 20), Neiguan (PC 6) and Taichong (LR 3)  with the reducing method and strong stimulation three times a week, acupressure on the Taichong (LR 3) twice a day for 30 times pressure and auricular acupressure on ear Shenmen, twice a day for 5 minutes. Result: Biochemical  mechanism of acupuncture and acupressure involve the stimulation of acupoint that lead to complex neuro-hormonal response. In handling hemifacial spasm, acupunture given for 15 times, taken three times a week combined with acupressure and auricular acupressure. This therapy overcome the symptoms of facial twitching in hemifacial spasm. Conclusion: Acupuncture combined with acupressure and auricular acupressure can be used to overcome facial twitching in hemifacial spasm.